The Historical Dynamics of the Samaniyyah Sufi Order in Pulo Bargot Village, Marbau District, 1950–2025: A Socio-Religious Perspective - Rahmat Alhafiizh; Hotmatua Paralihan (Medan Resource Center, 2026)
This study examines the early emergence and subsequent development of the Samaniyyah Sufi order in Pulo Bargot Village, Marbau District, from 1950 to 2025. The research is grounded in the recognition that Sufi orders function not only as spiritual practices but also as influential social forces within local communities. The study employs a qualitative historical approach, utilizing data collected through interviews with religious leaders and community members, complemented by written sources such as books and scholarly journals. The analysis follows the stages of heuristic, source criticism, interpretation, and historiography. The findings reveal that the Samaniyyah order began to develop around 1950 through recitation and dhikr practices introduced by local religious figures, with more significant expansion occurring after 2005 through the institutionalization of collective rituals such as communal dhikr, suluk, and other religious traditions. This study contributes to the historiography of local Sufism by demonstrating how a regional tarekat adapts to socio-religious dynamics while sustaining both spiritual authority and social cohesion within the community.